KEBUTUHAN RUANG TRANSISI DI KAWASAN CBD KOTA BANDUNG BERDASARKAN PREFERENSI DAN PERSEPSI PEJALAN KAKI - Witanti Nur Utami; Petrus Natalivan Indradjati; Heru Wibowo Poerbo (Diponegoro University, 2018)
City center is an urban place which always attract people either for visit or work purpose. Those activities generates pedestrian traffic that needs to be managed by providing transition space. So far, the need of transition space in urban Indonesia has not been clearly regulated and considered related to the design of transition space that can be use by pedestrians in the city center. Furthermore, there are no studies related to the aspects that need to be considered in the design needs of urban transition space from pedestrians point of view. The study aims to design transition space requirements in the CBD through a visitor and worker pedestrian preferences approach. Moreover, physical aspect / design element that need to be considered are conditions, potentials and factors that affect the existence of transition place. Field study and analysis found that visitor and workers found in Bandung central area mostly prefer pedestrian mall type as a transition space. Furthermore, the design principles for transition space consists of component of form, access and the character of space.